KONSEP PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR’AN SURAH LUQMAN AYAT 12-19 - Fitriana Fitriana (Universitas Muhammadiyah Tangerang, 2019)
Islamic education is essentially oriented towards religious and worldly goals, namely to form a generation of robbani who are obedient to the laws of God, and are able to face all forms of life challenges that exist, so that their lives become benefits for themselves and their environment. which is always appropriate for every age and place, provides guidance and direction in all areas of life in general, as well as in the principles and concepts in the field of education in particular. Among them as contained in the luqman chapter 12-19 which gives details of the basic concept of Islamic education as a whole; includes aqeedah, sharia and morality.Keywords: Concept, Islamic Education, Al-Qur'an, Surah Luqman Verses 12-19.